Reviewing the English for academic purposes curriculum: a preliminary analysis from the students’ perspective - Md Zamin, Ainul Azmin; Mohd. Asraf, Ratnawati (American Scientific Publishers, 2017)
This paper describes the results of a study on students' perceptions towards an English for Academic Purposes (EAP) course at tertiary level as part of a needs analysis prior to the course evaluation. Specifically, the study aimed to explore the students' attitude towards the various aspects of the EAP curriculum in order to improve the syllabus. A total of 139 students were involved in responding to a survey containing questions on various aspects; from course outline to textbooks. It was found that students were generally positive towards the course but they expressed concern over the use of textbook that were not directly relevant to their area of study. The students also highlighted the need to learn how to read critically. The other aspect of concern was the seminar skills where they did not properly learn about note-taking or participating in seminars. These results have some implications to the curriculum and the teaching pedagogy.